2010
DOI: 10.1021/jp1004852
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Reactivity Properties of Aun (6 ≤ n ≤ 13) Clusters Using Density Functional Theory Based Reactivity Descriptors

Abstract: Relativistic density functional theory (DFT) based calculations have been performed on gold clusters with six to thirteen atoms (Au n ; n = 6−13). The ground state geometries of these clusters as obtained from our calculations are presented and discussed. This work proposes that atoms in a ground state conformation can be classified into distinct types of reactive sites in a given geometry. Based on symmetry, susceptibility of various types of reactive sites in the ground state geometry toward an impending ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 74 publications
0
19
0
2
Order By: Relevance
“…105 The results of our calculations demonstrate that preferable sites for H 2 adsorption are the positively charged low-coordinated gold atoms in the most stable gold isomers. However, many of these sites are not the best for H 2 dissociation.…”
Section: ■ Results and Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…105 The results of our calculations demonstrate that preferable sites for H 2 adsorption are the positively charged low-coordinated gold atoms in the most stable gold isomers. However, many of these sites are not the best for H 2 dissociation.…”
Section: ■ Results and Discussionmentioning
confidence: 72%
“…It has been suggested that as a general rule the size and shape of the cluster influence the number and position of available sites for an electrophilic and/or nucleophilic attack. 105 This makes the reactivity patterns of these clusters highly complex.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For this purpose, we first optimize the structures of the above-mentioned three isomers of the Au 7 cluster at both PBE and TPSS levels, which are provided in the Supporting Information in ascending order of their energies. In conformity with earlier reported data, 39,51,58,59 we also find that planar geometry with C s symmetry represents the ground state of the Au 7 cluster.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is consistent with the conclusion reported in the literature. [56][57][58][59][60][61][62] It is reasonable that the substrate surface exerts an important role in determining the structure of supported Au x clusters. Without metal oxide substrate, the structures of Au x clusters will be just determined by the AuÀAu bond strength and arrangement.…”
Section: Effect Of Surface On Au X Cluster Structuresmentioning
confidence: 99%